Mitanni - Hittite Treaties During the Period (1480-1270 BC) (Raparin Journal of Humanities (RJH), 2023)
This research deals with the Mitanni - Hittite treaties during the period (1480-1270 BC), those treaties that had a great impact on the political and economic situation on the two kingdoms, especially the Mitanni kingdom. Where the Mitanni were at the beginning of the formation of their kingdom and during the period of the treaties, in a position of power so that it can be said that this type of treaties between two parties takes the form of equivalent treaties. However, the political conditions of the Mitanni kingdom have changed and its conditions have become bad as a result of the internal divisions between the ruling family, which in turn led to the pursuit of each of its princes wishing to ascend the throne to search for an ally against the other princes, in order to reach power. Therefore, treaties were made with neighboring powers hostile to the Mitanni kingdom, such as the Hittite kingdom as well as the Assyrian kingdom. The result of these treaties was that the Mitanni kingdom lost its complete independence and became subject to dependency. The final result was that it was completely eliminated by the Assyrians .